Switching in Bilinguals: Evidence from Forward and Backward Switching Tasks Across Visual and Auditory Modality - Aslin; Jilda Sulthana; Fathima Mehjabin; Abhishek B.P (Emerging Trends in Languages, 2024)
Bilingualism refers to the use of two languages on a day-to-day basis. Defining bilingualism operationally is complex due to the heterogeneity associated with it. Proficiency in the second language can vary on an individual basis. Bilinguals can be classified as balanced or dominant, high proficient or low proficient based on the proficiency levels. The effect of bilingual proficiency on executive functions has been studied extensively. The current study explored the switching ability. Switching refers to the ability to switch from one language to another language from L1-L2 and L2-L1 and this phenomenon refers to forward and backward switching. The current study investigated the effect of proficiency and modality on language switching. 30 Female participants in the age range of 18-30 years were included in the study. High proficient bilingual Participants were asked to switch the information presented in visual and auditory modality from L1to L2 and L2 to L1. The results showed that the performance on L1-L2 was superior compared to L2-L1 and the results were against the traditional claim that there would be no difference in forward and backward switching in balanced bilinguals. The results did not vary as a function of modality. The results signified the role of linguistic use over proficiency in determining the efficacy of switching. The result signifies that factors beyond the proficiency may influence executive function and the use of L2 in day-to-day context is one such potential factor which may have influenced the results.
Keywords: Backward Translation; Bilingualism; Executive function; Forward translation; Language Use; Proficiency